The moderating role of profitability in predicting financial distress in companies within the property and real estate sector - Boru Hotang, Keri (President University Press, 2025)
The purpose of this study is to provide empirical evidence through a purposive sampling approach to understand the role of profitability when a company is experiencing financial constraints and to predict the influence of leverage, company size, and sales growth. Data testing was conducted on 13 property and real estate companies listed on the Indonesia Stock Exchange (IDX) in the period 2014-2024. Data analysis used partial and moderation tests. The results of the data testing indicate that leverage and company size have an impact on financial distress, but this does not correspond to sales growth, which has no impact on financial distress. Furthermore, profitability is proven unable to moderate leverage and sales growth on financial distress, while company size weakens the impact on financial distress.